Contact Zones in the Eastern Mediterranean: Judeans and their neighbours in intercultural contexts: places, middlemen, transcultural contacts. –– Sixth to Second Century BCE - Wilimowska, Joanna; Sandowicz, Małgorzata; Nömmik, Urmas; Grassi, Giulia Francesca; Silverman, Jason M.; Honigman, Sylvie; Niesiołowski-Spanò, Łukasz; Ziemba, Kacper; Nihan, Christophe; Bussmann, Richard (Mundus Orientis : Studies in Ancient Near Eastern Cultures, 2024)
This volume comprises ten articles written by scholars working on various topics connected to the intercultural relations of Judeans/Jews in the Achaemenid and early Hellenistic periods in Palestine and in the diaspora. Instead of presenting broad over-arching descriptions, it focuses on case studies of the said relations. The chapters written by historians, biblical scholars, archaeologists and papyrologists concern topics like interreligious influences, questions of social connectivity, material culture, literary practices and reactions to the policies of imperial elites. Discussed in the context of wider Achaemenid and Hellenistic world and their history, the volume will serve as an invaluable read for all the scholars and students of Judean/Jewish history and intercultural relations in the ancient Mediterranean.